RISK MANAGEMENT COMMITTEES' INDICATORS AMONG CHINESE PUBLIC LISTED COMPANIES - Xin Miaoquan; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
After many company catastrophes, the board of directors' financial and non-financial risk management has garnered attention. Thus, the risk management committee (RMC) is becoming a board-level subcommittee to help the board of directors fulfil its role. This thesis studies the causes of RMC in Chinese public-listed firms. This study examines the relationship between RMC and board features such as independence, CEO duality, size, directorship, meeting, and competence. We evaluated six hypotheses in this study. Annual reports of all firms listed on Bursa China's Main Market for the 2009 financial year were used, except for financial institutions, which are regulated differently. The total sample had 797 firms. This study used logistic regression, as in previous investigations. This study shows that RMC positively correlates with board features such as board size and independent director outside directorships. Other control factors like corporate size and leverage are positively associated with RMC. Company boards of bigger size are more likely to form RMC. Companies with more independent directors use combined RMC for risk governance. Governance theory, particularly agency theory, is somewhat supported by the data, suggesting board monitoring aligns principals' and agents' different interests. This study may help regulators, politicians, and other stakeholders adopt or strengthen risk management reporting standards, especially in developing nations. This report should also encourage the industry to establish an RMC as a governance support tool for risk oversight.